Blood warming in trauma related transfusions-Precepts and practices - Indrani Ghosh; Rudrashish Haldar (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Trauma patients often have a high incidence of hypothermia which is secondary to prolonged exposures, surgery and anaesthesia induced alteration of thermal homeostasis and infusion of cold fluids during resuscitation. Transfusion of red blood cells and blood products (except platelets) which are stored at low temperatures compound the situation by causing a further decrement in the core body temperatures. The resultant hypothermia is detrimental as it involves majority of the organ systems and causes numerous deleterious effects like wound infection, platelet dysfunction and arrythmias, which complicates the clinical scenario. To avoid hypothermia and the resultant undesirable physiological consequences, it is imperative to warm the blood and blood products prior to transfusion. This article highlights the adverse effects of blood transfusion associated hypothermia and briefly discusses the available practices of warming of blood and blood products along with their merits and demerits.